2010
DOI: 10.1002/humu.21228
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of mutations in the ATP loop of the Wilson disease copper transporter, ATP7B

Abstract: Wilson disease (WND) is an autosomal recessive disorder resulting from mutation of ATP7B. Transport of copper by ATP7B from the trans-Golgi of hepatocytes into apical membrane-trafficked vesicles for excretion in the bile is the major means of copper elimination from the body. Although copper is an essential nutrient, homeostasis must be carefully maintained. If homeostasis is disrupted, copper can accumulate within the liver, kidney, cornea, and/or brain. The range of organs affected leads to clinical heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…A number of studies have investigated whether these variants are really disease-causing mutations rather than rare normal variants, highlighting that ATP7B mutations in the same protein domain can have diverse functional effects. [29][30][31][32] Nevertheless, it is possible to evaluate the pathogenetic potential of our LD blocks using the Wilson Disease Mutation Database to calculate the density of For the descriptive characteristics p < 0.05 (*) and p < 0.01 (**) are considered significant, whereas for ATP7B genotypes p < 0.017 (*) and p < 0.003 (**) are significant according multiple test correction.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated whether these variants are really disease-causing mutations rather than rare normal variants, highlighting that ATP7B mutations in the same protein domain can have diverse functional effects. [29][30][31][32] Nevertheless, it is possible to evaluate the pathogenetic potential of our LD blocks using the Wilson Disease Mutation Database to calculate the density of For the descriptive characteristics p < 0.05 (*) and p < 0.01 (**) are considered significant, whereas for ATP7B genotypes p < 0.017 (*) and p < 0.003 (**) are significant according multiple test correction.…”
Section: Discussionmentioning
confidence: 99%
“…A few metals like Ca 2+ and Mg 2+ which are similar in concentration in blood plasma and bile, may enter bile by a paracellular pathway by diffusion across the tight junctions (73). A P-type ATPase, ATP7B, is required for the biliary excretion of copper and is mutated in Wilson’s disease (98, 217, 345, 465, 544). This protein is localized to the trans -Golgi apparatus and nearby vesicles (241).…”
Section: Transport and Excretion Of Specific Substancesmentioning
confidence: 99%
“…An increasing number of studies use the predicted impact in a variety of applications, and have reported that SNV impact predictions match experimental findings 130,132,133. Such applications include guiding mutagenesis,134,135 identifying disease associated genes in both Mendelian and common diseases,1,136139 separating disease-causing variants from linkage disequilibrium variants,140 identifying somatic mutations that drive cancer,65,141,142 and predicting the overall phenotype of an organism 143.…”
Section: Applicationsmentioning
confidence: 99%